Quantitative Techniques for Internal Auditing (Book). - Barkman, Arnold I.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews the book "Quantitative Techniques for Internal Auditing," by Donald E. Ricketts and Horton L. Sorkin.